GAMBARAN ATAS FAKTOR-FAKTOR YANG BERPERAN DALAM MEMPENGARUHI KEPUASAN KERJA KARYAWAN (Studi pada Pegawai Perusahaan Rokok Jaya Makmur Bagian Produksi Bulanan Kepanjen Malang) - Ayu Firdiana Rahmania (Jurnal Administrasi Bisnis, 2013)
The objective of research is to describe and to explain the degree of the factors influencing work satisfaction of the employees of Jaya Makmur Cigarette Company, Production Division of Kepanjen Malang. Research type is description study with questionnaire as the main instrument of research. The population of research within Jaya Makmur Cigarette Company is 263 regular employees at production division who receive monthly salary. The sample is 159 employees. Result of analysis indicates that the variabel of work satisfaction with the highest mean is payment variabel with mean 4,1, and it is followed by co-worker variabel with mean 4,0, supervisor variabel with mean 3,8, promotion opportunity variables with the highest deviation standard is work variabel with 0,63, followes by supervisor variabel with 0,55, then work opportunity variabel with 0,52, co-worker variabel with 0,48, and lastly, payment variabel with 0,43. Research concludes that a factor with the greatest role in influencing the work satisfaction of employees of Jaya Makmur Cigarette Company is payment, and then it is followed by other factors such as co-worker, supervisor, promotion opportunity and work. Keyword: Work Satisfaction